Diaphragmatic CMAP Monitoring During Cryoballoon Procedures: Surface vs. Hepatic Recording Comparison and Limitations of This Approach - Tovmassian, Lilith; Maille, Baptiste; Koutbi, Linda; Hourdain, Jérôme; Martinez, Elisa; Zabern, Maxime; Deharo, Jean-Claude; Franceschi, Frédéric (Frontiers in Cardiovascular Medicine, 2022)
Background: Compound motor action potential (CMAP) monitoring is a common method used to prevent right phrenic nerve palsy during cryoballoon ablation for atrial fibrillation. Objective: We compared recordings simultaneously obtained with surface and hepatic electrodes. Methods: We included 114 consecutive patients (mean age 61.7±10.9 years) admitted to our department for cryoballoon ablation. CMAP was monitored simultaneously with a hepatic catheter and a modified lead I ECG, whilst right phrenic nerve was paced before (stage 1) and during (stage 2) the right-sided freezes. If phrenic threat was detected with hepatic recordings (CMAP amplitude drop >30%) the application was discontinued with forced deflation. Results: The ratio of CMAP/QRS was 4.63 [2.67-9.46] for hepatic and 0.76 [0.55-1.14] for surface (p<0.0001). Signal coefficients of variation during stage 1 were 3.92% [2.48-6.74] and 4.10% [2.85-5.96] (p=0.2177), respectively. Uninterpretable signals were more frequent on surface (median 10 vs 0; p<0.0001). For the 14 phrenic threats, the CMAP amplitude dropped by 35.618.27% on hepatic signal and by 33.4211.58% concomitantly on surface (p=0.5417). Our main limitation was to achieve to obtain stable phrenic capture (57%). CMAP monitoring was not reliable because of pacing instability in 15 patients (13.16%). A palsy occurred in 4 patients (3.51%) because cryoapplication was halted too late. Conclusion: Both methods are feasible with the same signal stability and amplitude drop precocity during phrenic threats. Clarity and legibility are significantly better with hepatic recording (sharper signals, less far-field QRS). The two main limitations were pacing instability and delay between 30% CMAP decrease and cryoapplication discontinuation.